GENETIC COUNSELING AND TESTING IN THE CONTEXT OF HEREDITARY BREAST CANCER: A STUDY OF PERCEPTIONS AMONG THE POPULATION OF GOIÁS (CIPEEX, 2026)
Introduction: Breast cancer is the most common and deadliest neoplasm among women worldwide. Between 5% and 10% of cases have a hereditary origin, mainly due to mutations in the BRCA1 and BRCA2 genes, which increase the risk and aggressiveness of the disease. Despite the relevance of genetic counseling and testing, barriers such as low awareness and limited access remain, especially in low- and middle-income countries. Objective: To assess the perceptions of the population of the state of Goiás regarding genetic counseling and testing for hereditary breast cancer, identifying perceived benefits, barriers, and resistance. Methods: Observational, cross-sectional, and quantitative study with 239 participants aged ≥18 years residing in Goiás. Data were collected through an electronic questionnaire containing 11 Likert-scale statements on aspects of genetic counseling. Statistical analysis was performed using the chi-square test to assess associations, with p
Keywords: breast neoplasms; genetic counseling; women's health